Strategic Positioning and Performance of Pharmacies within Kisumu City - Ngira, Johnstone Odhiambo; Juma, Dennis (Journal of Business and Strategic Management, 2025)
Purpose: The purpose of this research was to establish the influence of strategic positioning and cross border business performance of commercial banks in Kenya. The specific objectives of the study was to establish the influence of adaptive positioning, anticipatory positioning, defensive positioning and multi segment positioning on performance of pharmaceutical firms in Kisumu. The study used three theories including strategic positioning theory, administrative management theory and the theory of performance. Methodology: The study sampled 106 respondents from the 118 pharmacies in Kisumu. Purposive sampling was used to select the sample for the study. Questionnaires were used in collection of data. Descriptive statistics and multiple regression analysis were used to analyze the data. Findings: The study results revealed that adaptive, anticipatory, defensive and multi-segment positioning all had positive and statistically significant effect on the performance of Pharmacies in Kisumu City. Unique Contribution to Theory, Practice and Policy: The study recommends that organizations should periodically reposition a brand to follow the evolution of the segment's needs. They should also position new brands in anticipation of the evolution of a segment's needs. When a firm occupies a strong position in a market segment with a single brand, it is vulnerable to imitative positioning strategies so it should learn to defend its position. The firm may preempt competitive strategies by introducing an additional brand in a similar position for the same segment. Lastly, firms can also position a product so as to attract consumers from different segments. This is an attractive strategy since it provides higher economies of scale and so higher profits.